2017
DOI: 10.1186/s40621-017-0112-0
|View full text |Cite
|
Sign up to set email alerts
|

Do adolescents with long-term illnesses and disabilities have increased risks of sports related injuries?

Abstract: BackgroundThe aim of this study is to examine the rates of sports related injuries in adolescents based on the severity of their long-term illnesses or disabilities (LTID). Few injury prevention strategies in sports and health promotion have explored disaggregation by disability.MethodsData obtained from the 2014 Finnish Health Behaviour in School-aged Children survey (n = 3716, mean age = 14.8, SD = 1.03) were grouped into adolescents with and without LTID. A further indicator or severity was determined when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…A detailed Australian study showed a transient increase in bleeding risk in children and adolescents with moderate and severe hemophilia after vigorous physical activity but the absolute increase in bleeding risk was small 27 . A nationwide cross‐sectional study in Finland reported higher sports injury risk in adolescents with a chronic health condition (eg, asthma, diabetes, and joint pain) than in the general population 28 …”
Section: Introductionmentioning
confidence: 99%
“…A detailed Australian study showed a transient increase in bleeding risk in children and adolescents with moderate and severe hemophilia after vigorous physical activity but the absolute increase in bleeding risk was small 27 . A nationwide cross‐sectional study in Finland reported higher sports injury risk in adolescents with a chronic health condition (eg, asthma, diabetes, and joint pain) than in the general population 28 …”
Section: Introductionmentioning
confidence: 99%
“…Sports participation has important health benefits in both healthy youth and peers with chronic diseases or physical disabilities (CDPD) (1)(2)(3)(4)(5). Studies have shown strong associations between being member of a sports club and the amount of moderate-vigorous physical activity (MVPA) and vigorous activity levels (VPA) in youth with CDPD; those who are sport club members are twice as likely as nonmembers to meet international physical activity (PA) recommendations (4,6,7). Meeting adequate PA levels supports a healthier lifestyle.…”
Section: Single Statement Summarizing the Clinical Relevancementioning
confidence: 99%
“…Sports participation has important health benefits in both healthy youth and peers with chronic diseases or physical disabilities (CDPD) [1][2][3][4][5]. Studies have shown strong associations between being member of a sports club and the amount of moderate-vigorous physical activity (MVPA) and vigorous activity levels (VPA) in youth with CDPD; those who are sport club members are twice as likely as non-members to meet international physical activity (PA) recommendations [5][6][7]. Meeting adequate PA levels supports a healthier lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, sports participation is also known to lead to sports-related injuries and illnesses, as shown in adults, healthy youth and among youth with CDPD [5][6][7]. Sports injuries among healthy youth have a considerable impact on their participation and performance in subsequent activities [6,8].…”
Section: Introductionmentioning
confidence: 99%